2022
DOI: 10.1136/bmjopen-2022-066766
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody responses post-vaccination in UK healthcare workers with pre-existing medical conditions: a cohort study

Abstract: ObjectivesTo examine antibody responses after the second vaccination in healthcare workers (HCWs) with underlying health conditions.DesignCohort study.SettingOxford University Hospitals in the United Kingdom.ParticipantsHealthcare workers who had SARS-CoV-2 serological data available and received two SARS-CoV- 2 vaccinations.Primary outcomePeak SARS-CoV-2 anti-spike IgG responses after the second vaccination and associations with underlying health conditions and the estimated risk of severe COVID-19 using an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
2
3
1
Order By: Relevance
“…Our findings confirm previously reported associations between the following risks or characteristics and a suboptimal antibody response following vaccination (individuals may fall into more than one risk group): cancers 7 , 20 , 21 , obesity 7 , 22 , 23 , use of immunosuppressant therapies 6 , 20 , 21 , 24 , 25 , being on the shielded patient list 25 and age 6 , 7 , 26 . Our findings of a greater likelihood of testing negative for antibodies post-vaccination among specific clinical risk groups (those with kidney disease 7 , 27 , cirrhosis 28 , diabetes 7 , 29 , haematological cancers 30 32 , and neurological conditions 7 , 33 ) were also consistent with the published literature, although in some of these conditions a diminished immune response may be attributable to therapies used to treat the condition rather than the condition itself. We did not however observe any association between socioeconomic status or sex and antibody response – the latter finding in contrast to previously published results, which have demonstrated higher SARS-CoV-2 IgG levels among females 7 , 26 .…”
Section: Discussionsupporting
confidence: 90%
“…Our findings confirm previously reported associations between the following risks or characteristics and a suboptimal antibody response following vaccination (individuals may fall into more than one risk group): cancers 7 , 20 , 21 , obesity 7 , 22 , 23 , use of immunosuppressant therapies 6 , 20 , 21 , 24 , 25 , being on the shielded patient list 25 and age 6 , 7 , 26 . Our findings of a greater likelihood of testing negative for antibodies post-vaccination among specific clinical risk groups (those with kidney disease 7 , 27 , cirrhosis 28 , diabetes 7 , 29 , haematological cancers 30 32 , and neurological conditions 7 , 33 ) were also consistent with the published literature, although in some of these conditions a diminished immune response may be attributable to therapies used to treat the condition rather than the condition itself. We did not however observe any association between socioeconomic status or sex and antibody response – the latter finding in contrast to previously published results, which have demonstrated higher SARS-CoV-2 IgG levels among females 7 , 26 .…”
Section: Discussionsupporting
confidence: 90%
“…Our findings confirm previously reported associations between the following risks or characteristics and a suboptimal antibody response following vaccination (individuals may fall into more than one risk group): cancers 7,17,18 , obesity 7,19,20 , use of immunosuppressant therapies 6,17,18,21,22 , being on the shielded patient list 22 and age 6,7,23 . Our findings of a greater likelihood of testing negative for antibodies post-vaccination among specific clinical risk groups (those with kidney disease 7,24 , cirrhosis 25 , diabetes 7,26 , haematological cancers [27][28][29] , and neurological conditions 7,30 ) were also consistent with the published literature, although in some of these conditions a diminished immune response may be attributable to therapies used to treat the condition rather than the condition itself. We did not however observe any association between socioeconomic status or sex and antibody responsethe latter finding in contrast to previously published results, which have demonstrated higher SARS-CoV-2 IgG levels among females 7,23 .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, another UK HCW study found Black HCW to have lower serologic responses to vaccination than their White counterparts and found no differences between the White and Asian groups. 23 …”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 , 18 , 19 , 20 , 21 A recent study reporting findings from a large cohort of UK healthcare workers (HCWs) found higher SARS-CoV-2 anti-spike titres in ethnic minority vaccinees than in their White counterparts, 22 which contrasts with another UK HCW study which found lower peak anti-spike antibody titres in Black HCWs compared to White HCWs and did not find differences between the White and Asian groups. 23 A large UK observational study in the general population found South Asians vaccinees to have higher combined IgG, A and M titres against SARS-CoV-2 than those from White groups. 24 Crucially, there are no studies that present data relating to both cellular immune responses and SARS-CoV-2 neutralising activity after vaccination stratified by ethnicity.…”
Section: Introductionmentioning
confidence: 99%